Analisa Pengaruh Penggunaan Sensor Oksigen Terhadap Kandungan Emisi Gas Buang CO Dan HC - Dwi Sudarno Putra; Donny Fernandez -; Gito Gito Giantoro - (Jurnal Ilmiah Poli Rekayasa, 2015)
The use of oxygen sensors on vehicles intended to reduce the harmful content from vehicle exhaust emissions. Research and journal was prepared to find how much reduction can be achieved. Research conducted by the experimental method. This type of machine used is K3-VE engine Avanza. Measurements are performed using the exhaust emission analyzer Fourgas at some level of engine speed.        From the research proven when using oxygen sensors decrease harmful content of exhaust emissions. The decline in the percentage of the CO content of 1.86% and the average number of HC ppm reduced the total 258.33ppm.